Identifying constraining and enabling factors to the uptake of medium- and long-term climate information in decision making - Jones, Lindsey; Champalle, Clara; Chesterman, Sabrina; Cramer, Laura K.; Crane, Todd A. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
We apply a systematic review of peer-reviewed literature to assess constraining and enabling factors to the uptake of medium- to long-term climate information in a wide range of sectoral investment and planning decisions. Common applications of climate information are shown to relate to adaptation of environmental policy and planning, urban planning and infrastructure, as well as flood and coastal management. Analysis of identified literature highlights five categories of enablers to the uptake of medium- to long-term climate information in decision-making, the most of frequent of which relates to greater collaboration and bridging between producers and users of climate information. Five categories of constraints are also identified, the largest comprising of scientific and technical limitations associated with available medium- to long-term climate information.